Spectral and Theoretical Analysis of N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2yl]-N´-thiophen-2ylmethylene-Chloro-acetic Acid Hydrazide by DFT Method - Kanmazalp, Sibel Demir; Dinçer, Muharrem; Çukurovalı, Alaaddin; Yılmaz, Ibrahim (My University, 2019)
This study presents a combined experimental and theoretical research on an N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-N´thiophen-2ylmethylene-Chloro-acetic acid hydrazide compound. The optimized molecular structure, 1H and 13C chemical shift values and vibrational assignments of the titled compound were examined by depending on the density functional method and by using 6-31G(d), 6-31G(d,p) and 6-311G(d,p) basis sets. Moreover, HOMO–LUMO analysis and molecular electrostatic potential were carried out in order explore charge delocalization on this molecule.
Keywords: Fizik; Atomik ve Moleküler Kimya; Kimya; Organik; Fizikokimya